Minimally invasive transforaminal lumbar interbody fusion (MIS TLIF): 2 year prospective outcome study in a tertiary care hospital - Khai, Sing Lam; Mor Japar Khan, Ed Simor Khan (2015)
MIS TLIF is a safe and effective technique in our prospective clinical study of 91 patients that achieved good to excellent clinical outcomes above the expectations of the patient. All patients showed significant improvements in their ODI, VAS score, and SF-36 domains at every time point studied that was maintained up to 24 months. Once radiological healing takes place, the patients have a steady uphill course towards improved functional recovery and reduced pain.